2010
DOI: 10.1007/s00423-010-0654-x
|View full text |Cite
|
Sign up to set email alerts
|

Defect classification and reconstruction algorithm for patients with tracheostomy using the tunneled supraclavicular artery island flap

Abstract: The proposed classification and treatment algorithm provides a structured approach to a successful surgical treatment of this complex condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 17 publications
0
33
0
1
Order By: Relevance
“…It was a branch of the transverse cervical artery in 91% of anatomic dissections, arising from the suprascapular artery in fewer than 9% of cases (Table 1). [1][2][3][4][5]7,[11][12][13][14][15][16][17][18][19][20] Of the 146 anatomic dissections, only 2 (1.4%) were supraclavicular artery anomalies. The distance between the sterno- …”
Section: Anatomic Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was a branch of the transverse cervical artery in 91% of anatomic dissections, arising from the suprascapular artery in fewer than 9% of cases (Table 1). [1][2][3][4][5]7,[11][12][13][14][15][16][17][18][19][20] Of the 146 anatomic dissections, only 2 (1.4%) were supraclavicular artery anomalies. The distance between the sterno- …”
Section: Anatomic Studiesmentioning
confidence: 99%
“…The supraclavicular flap has been used for the coverage of defects over the sternum, neck, trachea, retroauricular area, cheek, and oral cavity. [1][2][3] was the first to describe the supraclavicular flap in 1979; this flap was subsequently popularized by Pallua and Wolter, 1 Chiu et al, 2 Pallua and Demir, 3 and Vinh et al 5 The pedicled supraclavicular flap is a very reliable flap, although some investigators have noted rare vascular anomalies that may lead to flap complications. Vinh et al 5 reported the use of the posterior circumflex humeral artery to supercharge large flaps harvested beyond the vascular territory of the supraclavicular flap.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…5 This flap was subsequently popularized in head and neck reconstruction by others including Pallua and Magnus Noah and Chiu et al 6,7 The SCAF has been described for multiple sites of reconstruction including oral cavity, trachea, pharynx, and skin defects. [6][7][8] Advantages of the flap are the ease of harvest, minimal donor site morbidity, and lack of microvascular anastomosis.…”
Section: Introductionmentioning
confidence: 99%
“…and the postauricular island flap (flip-flop-flap) has been frequently discussed in the repair of anterior auricular defects in which skin and cartilage have been excised [16][17][18]. Of course, tunneled flaps are well-known techniques in reconstructive facial surgery, and even very large facial defects can be repaired with flaps harvested from remote sites and tunneled under the remaining facial skin between the flap's donor site and the primary surgical defect 19,20. …”
mentioning
confidence: 99%